SafeSteps: a persuasive child pedestrian safety learning mobile application / Nadia Abdul Wahab ... [et al.] - Abdul Wahab, Nadia; Azhar, Muhammad Aiman; Osman, Aznoora; Ibrahim, Norfiza; Seman, Azmi Abu; Md Ilyas, Siti Sarah (UiTM Cawangan Perlis, 2024)
This study focuses on the design, development, and evaluation of SafeSteps, a mobile application dedicated to child pedestrian safety. Employing multimedia elements, SafeSteps imparts knowledge on pedestrian safety to children, with an integrated quiz module enhancing learning activities. The project development adhered to the Waterfall Model Methodology, encompassing distinct stages of analysis, design, implementation, testing, and documentation. Guided by the principles of persuasive technology and multimedia, the application was developed using Android Studio as the Integrated Development Environment (IDE) tool. A User Experience Testing (UXT) involving 31 children aged six to twelve aimed to assess engagement, identify usability concerns, and discover areas for enhancement. Utilizing the User Experience Questionnaire (UEQ), the study gathered feedback, revealing a majority expressing a positive perception of SafeSteps in terms of attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. The UXT findings offer significant insights into user perceptions and interactions with SafeSteps. This information will be instrumental in identifying potential areas for improvement, implementing design modifications, and enhancing the overall user experience of the mobile application, emphasizing the importance of incorporating multimedia and interactive elements in child pedestrian safety interventions